PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN RAWAT JALAN RUMAH SAKIT LUDIRA HUSADA TAMA YOGYAKARTA: - - Y.B. Arya Primantana; Rini Dwiastuti (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
This study analyzes the effect of service quality on outpatient loyalty through patient satisfaction at RS Ludira Husada Tama Yogyakarta. Using purposive sampling, 150 outpatients completed SERVQUAL-based questionnaires analyzed with SEM-PLS. Results showed that tangible (p=0.017) and assurance (p=0.002) dimensions significantly influenced patient satisfaction, while reliability (p=0.554), responsiveness (p=0.646), and empathy (p=0.902) did not. Patient satisfaction significantly influenced loyalty (p=0.001). The findings indicate that physical facilities and service assurance are critical factors in building patient loyalty through satisfaction in outpatient settings.. Keywords: service quality, patient satisfaction, patient loyalty, outpatient, SERVQUAL